IMPROVING STUDENTS’ WRITING SKILL ON PERSONAL RECOUNT TEXT THROUGH PEER ASSESSMENT - Istiqomah, Laely; Apriliaswati, Rahayu; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The research purpose was to improve students’ writing skill on personal recount text through peer assessment on the tenth grade students of SMA Muhammadiyah 1 Pontianak in academic year 2016/2017. The research subjects were the English teacher and 40 students of X MIA 2 class. The data were collected through field note, observation checklist, students’ and teacher’s interview, and students’ writing on personal recount text. The findings showed several improvements. First, the students’ were able to identify and assess their peer’s writing by giving comment and suggestion through peer assessment sheet as the guidance. Second, the students’ interactions between themselves were improved since they need to clarify the suggestions and comments to revise their writing. Third, the improvement of the students’ writing on personal recount text was proven by the increase of the mean score in each cycle. In the first cycle, the mean score was 72.5, in the second cycle the mean score was 81.85 and in the third cycle the mean score was 86.62. Since the mean score of each cycle increased, therefore this research showed peer assessment improved students’ writing skill on personal recount text. Keywords  : Peer Assessment, Writing Skill, Personal Recount Text Abstrak : Penelitian ini bertujuan untuk meningkatkan kemampuan menulis teks personal recount melalui penilaian sejawat terhadap siswa kelas X SMA 1 Muhammdiyah 1 Pontianak tahun ajaran 2016/2017. Metode penelitian ini adalah Penelitian Tindakan Kelas. Subjek penelitian ini adalah guru bahasa inggris dan 40 siswa kelas X MIA 2. Pengumpulan data menggunakan catatan lapangan, observasi, interviu, dan tulisan teks personal recount siswa. Temuan penelitian menunjukan beberapa peningkatan. Pertama, siswa dapat mengidentifikasi dan menilai tulisan teman sejawat dengan memberikan komentar dan saran melalui lembar penilaian sejawat sebagai pedoman. Kedua, interaksi sesama siswa meningkat karena mereka perlu untuk mengkalifikasi saran dan komentar untuk memperbaiki tulisan mereka. Ketiga, peningkatan kemampuan menulis siswa dibuktikan oleh kenaikan nilai rata-rata siswa ditiap siklus. Pada siklus pertama, nilai rata-rata yang diperoleh adalah 72,5, kemudian mencapai 81.85 disikus kedua, dan meningkat menjadi 86.62 disiklus ketiga. Oleh karena nilai rata-rata siswa meningkat, dapat disimpulkan bahwa penelitian ini menunjukkan penilaian sejawat meningkatkan kemampuan menulis siswa terhadap teks personal recount. Kata Kunci      : Penilaian sejawat, Kemampuan Menulis, Teks Personal Recount